Outcomes of osteosarcoma, chondrosarcoma and chordoma treated with image guided-intensity modulated radiation therapy. (November 2021) - Laskar, Siddhartha; Kakoti, Sangeeta; Khanna, Nehal; Manjali, Jifmi Jose; Mangaj, Akshay; Puri, Ajay; Gulia, Ashish; Nayak, Prakash; Pai, Prathamesh; Nair, Deepa; Qureshi, Sajid; Chinnaswamy, Girish; et al.
Highlights: Dose-escalated IG-IMRT results in good LC & CSS in OGS, CS and CH of H&N and pelvis. No significant difference in outcomes for definitive versus post-operative RT. Significant and sustained benefit in functional outcomes after RT. Acute & late toxicities were minimal despite escalated doses. Salvage re-RT is feasible and efficacious in recurrence after dose-escalated IG-IMRT. Abstract: Background & purpose: To evaluate the efficacy and toxicity of dose-escalated image guided-intensity modulated radiation therapy (IG-IMRT) in osteosarcoma (OGS), chondrosarcoma (CS) and chordoma (CH) of head and neck (H&N) and pelvis. Methods and Materials: In this prospective non-randomized study, 65 patients of H&N or pelvic OGS (24), CS (7) and CH (34) mandating definitive or post-operative radiotherapy from May 2013 to December 2018 were included. Radiotherapy doses in definitive setting were 72.0 Gy for CH and 70.2 Gy for OGS and CS; while in post-operative setting it was 66.6 Gy and 64.8 Gy respectively (at 1.8 Gy per fraction). Results: Planned doses of radiotherapy could be completed in 61 (93.8%) patients; with grade III or higher acute and late toxicities of 3% and 0% respectively. With a median follow-up of 52 (range 6–92) months, the five-year actuarial local control (LC) rates were 66% in OGS, 38.1% in CS and 75.9% in CH; while cause-specific survival (CSS) rates were 54.7%, 64.3% and 92.2% respectively. There was no statistically significant difference in outcomes for patients receiving definitive and post-operative radiotherapy. Locally controlled disease at first follow-up after radiotherapy was associated with improved CSS and OS in CS ( p = 0.014) and CH ( p < 0.001). Radiotherapy resulted in significant and sustained improvement in Musculoskeletal tumour society (MSTS) score and reduction in pain score. Salvage re-irradiation was feasible in local progression after radiotherapy, with good outcomes and tolerability. Conclusion: Dose-escalated IG-IMRT results in good LC & functional improvement with minimal toxicity in OGS, CS and CH.